1995
DOI: 10.1111/j.1365-3148.1995.tb00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet phenotyping in carriers for Glanzmann's thrombasthenia: a simple screening test for assessment of the molecular defect

Abstract: Glanzmann's thrombasthenia (GT) is a recessive autosomal bleeding disorder characterized by the abnormality of aggregation due to a platelet glycoprotein (GP) IIb-IIIa deficiency or a dysfunctional complex. Molecular abnormalities have been localized on the gene coding for GP IIb or IIIa. The aim of our work was an attempt to obtain indirectly information on the putative localization of the molecular defect in patients with GT type I or II by the determination of the HPA-1 (GP IIIa) and HPA-3 (GP IIb) alloanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The presence of such a high incidence of the HPA‐1b genotype in gypsy patients, all homozygous for the same GT mutation, strongly suggests that the gypsy mutation first arose on a chromosome that also encoded the Pro33 form of β3. As well as our own genotyping (see above), previous authors have examined the expression of the HPA‐1a (Pl A1 ) alloantigen on platelets in gypsy families in France known to contain the GT mutation and obligate heterozygotes with 50% expression of αIIbβ3 were located that bound anti‐HPA‐1a antibody in amounts consistent with the presence of a single wild type Leu33 allele [14,15]. This adds weight to our conclusion that our results are not due simply to an unusual dominance of HPA‐1b in the Manouche gypsies per se .…”
Section: Resultssupporting
confidence: 71%
“…The presence of such a high incidence of the HPA‐1b genotype in gypsy patients, all homozygous for the same GT mutation, strongly suggests that the gypsy mutation first arose on a chromosome that also encoded the Pro33 form of β3. As well as our own genotyping (see above), previous authors have examined the expression of the HPA‐1a (Pl A1 ) alloantigen on platelets in gypsy families in France known to contain the GT mutation and obligate heterozygotes with 50% expression of αIIbβ3 were located that bound anti‐HPA‐1a antibody in amounts consistent with the presence of a single wild type Leu33 allele [14,15]. This adds weight to our conclusion that our results are not due simply to an unusual dominance of HPA‐1b in the Manouche gypsies per se .…”
Section: Resultssupporting
confidence: 71%
“…In patients with these disease, molecular abnormalities have been noted on the gene coding for glycoprotein lib or Ilia. 4 Pregnancy and delivery are rare in these patients and have been associated with a high risk of severe hemorrhage. 5 " 10 We present an unusual case in which a primigravida patient with Glanzmann's thrombasthenia underwent an uneventful pregnancy and spontaneous vaginal delivery following intrapartum administration of singledonor platelets.…”
mentioning
confidence: 99%
“…Patient CN is a female Glanzmann thrombasthenia type II patient who has previously been reported by us (19)(20). Clinically, the patient had mild hemorrhagic manifestations such as petechia or ecchymosis on the legs and some menorrhagia.…”
Section: Case Reportmentioning
confidence: 84%
“…We have previously shown that human platelet antigen (HPA) phenotyping of carriers for Glanzmann's thrombasthenia can help to identify the defective gene responsible for GT. Phenotyping of the human platelet alloantigen systems HPA-1 (GP IIIa) and HAP-3 (GP IIb) in the available family members of patient CN revealed that the patient's mother as well as her son were heterozygous for the HPA-3 alloantigen system, suggesting normal expression of the two GPIIb alleles and possibly a defective GP IIIa gene (20). In order to further characterize the molecular defect responsible for the GT phenotype of patient CN, genomic DNA was prepared and the coding exons of GPIIb and GPIIIa amplified and sequenced.…”
Section: Identification Of the Thrombasthenic Mutation In Patient Cnmentioning
confidence: 99%